Positive regulation of osteogenesis by bile acid through FXR. (18th September 2013) - Cho, Sun Wook; An, Jee Hyun; Park, Hyojung; Yang, Jae‐Yeon; Choi, Hyung Jin; Kim, Sang Wan; Park, Young Joo; Kim, Seong Yeon; Yim, Mijung; Baek, Wook‐Young; Kim, Jung‐Eun; Shin, Chan Soo
ABSTRACT: Farnesoid X receptor (FXR) is a nuclear receptor that functions as a bile acid sensor controlling bile acid homeostasis. We investigated the role of FXR in regulating bone metabolism. We identified the expression of FXR in calvaria and bone marrow cells, which gradually increased during osteoblastic differentiation in vitro. In male mice, deletion of FXR (FXR −/− ) in vivo resulted in a significant reduction in bone mineral density by 4.3% to 6.6% in mice 8 to 20 weeks of age compared with FXR +/+ mice. Histological analysis of the lumbar spine showed that FXR deficiency reduced the bone formation rate as well as the trabecular bone volume and thickness. Moreover, tartrate‐resistant acid phosphatase (TRACP) staining of the femurs revealed that both the osteoclast number and osteoclast surface were significantly increased in FXR −/− mice compared with FXR +/+ mice. At the cellular level, induction of alkaline phosphatase (ALP) activities was blunted in primary calvarial cells in FXR −/− mice compared with FXR +/+ mice in concert with a significant reduction in type I collagen a1(Col1a1), ALP, and runt‐related transcription factor 2 (Runx2) gene expressions. Cultures of bone marrow–derived macrophages from FXR −/− mice exhibited an increased number of osteoclast formations and protein expression of nuclear factor of activated T cells, cytoplasmic 1 (NFATc1). In female FXR −/− mice, although bone mineral density (BMD) was not significantly different from that in FXR +/+ mice, bone loss was accelerated after an ovariectomy compared with FXR +/+ mice. In vitro, activation of FXR by bile acids (chenodeoxycholic acid [CDCA] or 6‐ECDCA) or FXR agonists (GW4064 or Fexaramine) significantly enhanced osteoblastic differentiation through the upregulation of Runx2 and enhanced extracellular signal‐regulated kinase (ERK) and β‐catenin signaling. FXR agonists also suppressed osteoclast differentiation from bone marrow macrophages. Finally, administration of a farnesol (FOH 1%) diet marginally prevented ovariectomy (OVX)‐induced bone loss and enhanced bone mass gain in growing C57BL/6J mice. Taken together, these results suggest that FXR positively regulates bone metabolism through both arms of the bone remodeling pathways; ie, bone formation and resorption. © 2013 American Society for Bone and Mineral Research.